Generation of Porous Alumina Layers in a Polydimethylsiloxane/Hydrogen Peroxide Medium on Aluminum Substrate in Corona Discharges. (3rd September 2014) - Groza, A.; Surmeian, A.; Diplasu, C.; Luculescu, C.; Negrila, C.; Ganciu, M.
Abstract : The porous alumina (Al2 O3 ) layer obtained at the interface between polydimethylsiloxane/hydrogen peroxide medium and aluminum substrate under charged and neutral species injection produced in negative corona discharges in air at atmospheric pressure is analyzed by different methods in this paper. The scanning electron microscopy investigations showed the uniform distribution of the pores formed in the alumina layer and their columnar structures. Both energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS) measurements indicate that during the anodization process of the aluminum in the polydimethylsiloxane/hydrogen peroxide medium in corona discharge the incorporation of silicon in the structure of the alumina layer is possible.